Investigation of continuous PAN nanofiber yarn produced with polymer additives - Borazan, Ismail (Taylor & Francis Ltd, 2023)
Nanofiber yarns were produced by electrospinning technique from polyacrylonitrile (PAN), thermoplastic polyurethane (TPU) added and polyvinylidene fluoride (PVDF) added PAN polymer solutions. The effects of the other polymers as additive to PAN nanofiber yarn are investigated. SEM, stress-strain characterizations were carried out. A sample plain fabric was woven from PAN nanofiber yarns to show that nanofiber yarns are feasible and can be integrated into conventional textile structures. Addition of the other polymers has increased the Young modulus by 40%, whereas TPU addition has increased the tenacity by 50% but TPU + PVDF addition has decreased the tenacity by half of only PAN. Breaking elongation was slightly decreased by the addition of TPU and PVDF polymers.
Keywords: Nanofiber yarn; electrospinnning; polymer composite; PAN; TPU; PVDF